Depositional Environment of Deep-Water Fan Facies: A Case Study of the Middle Miocene Interval at the Kutei and North Makassar Basins - Kuntadi Nugrahanto; Ildrem Syafri; Budi Muljana (Jurnal Geologi dan Sumberdaya Mineral, 2021)
Massive exploration effort in the study area was conducted in 1996-2014 when deep-water drilling campaign found significant oil and gas discoveries but yet to optimally reach the middle Miocene deep-water sandstone reservoirs. Outcrops, well bores and 2D-seismic data had been incorporated in this study. Datum age from several taxon indicators have been utilized to correlate and unify various markers across the study area into four key biostratigraphy markers: M40, M45, M50, and M65. These four markers are at that point tied to the 2D seismic data in the act of the main horizons in conducting the seismic stratigraphy analysis over the study area not reached by wells. Identifying candidate of sub-regional sequence boundaries onshore and offshore that correspond with relative sea-level drops are the main result of this study. These results were integrated to generate the deep-water fan facies of the middle Miocene's gross depositional environment (GDE) maps, which generally show prograding succession easterly in the various shelf-breaks shifting laterally. The angle of slope and the horizontal length of the shelf-to-slope breaks significantly change from the Middle to Late Miocene until Recent time.Keywords: GDE, deep-water fan, Middle Miocene, Kutei, North Makassar.